Spatial Variations in the Distribution of Benthic Macroinvertebrate Functional Feeding Groups in Tropical Rivers - Marielle Kristine Doong; Jonathan Anticamara; Francis Magbanua (Indonesian Society of Limnology, 2021)
Functional feeding group (FFG) is an approach that classifies macroinvertebrates based on their utilization of organic matter food resources. Across streams and rivers, variations in the distribution of FFGs reflect the unequal distribution of food resources, which are affected by varying environmental conditions and disturbances to the ecosystem. In the tropics, the distribution of FFGs does not follow the pattern observed in temperate streams. This study aims to (1) determine the FFGs present in selected Philippine tropical streams, (2) assess the variations in FFG distributions and how the distributions vary across space, and (3) evaluate how FFG distributions are affected by certain environmental factors and habitat structure. Benthic macroinvertebrates were collected in 2010 from five sites and assigned to their primary FFG based on published literature. Across study sites, the macroinvertebrates collected were classified into gathering collectors (total n = 4,640), scrapers (n = 1,670), filtering collectors (n = 1,545), predators (n = 632), and shredders (n = 270). Within and between sites, these FFGs varied significantly. Variations explained the upstream-downstream and north-south variations in the mean of FFG abundance in width and depth of the stream, discharge, temperature, pH, riparian vegetation, and habitat stability and variability. This study reveals that the FFG approach is a useful bioassessment tool in tropical aquatic systems. However, there is still a need for verification of the findings in other streams and seasons.